Comparison of the performance of flexible and roller-compacted concrete pavement structures - Mickevič, Rafal; Vaitkus, Audrius (International Conference “Environmental Engineering”, 2023)
Slip-form concrete (Joint plain concrete pavement) has number of years of good performance experience. As experience showed such technology is cost efficient only for high capacity roads, where very strict requirements for pavement roughness are defined. It also requires special knowledge, experience and mechanisms. An alternative to slip-form concrete is roller-compacted concrete (RCC). RCC mixture has significantly larger amount of fine aggregates, which leads concrete mix to be non-slip. RCC has the strength and performance of conventional concrete with the economy and simplicity of asphalt. Starting from 2016 Lithuania gain experience of RCC pavement structures with cement and special additives bounded base. Asphalt and RCC pavement structures are very competitive. It is very important to make study of the bearing capacity of RCC pavement structures and compare with asphalt pavement structures to know how they perform on the site.